An Analysis of the Second Year Students’ Ability in Writing a Procedure Text about a Recipe at SMK N 9 Padang - Tari Kurnia Putri; Saunir Saun (Universitas Negeri Padang, 2019)
This research was about the students' ability in writing a procedure text, with the topic of how to make a cake. This study aimed to determine the level of students' ability to write procedure texts seen from the generic structure and language feature of the text. The research design was the descriptive research. The population of this study was all students of class XI, majoring in Culinary of SMKN 9 Padang. The population was 122 students from 8 classes, XI K1, XI K2, XI K3, XI K4, XI K5, XI K6, XI K7, and XI K8. The sample was taken by random sampling technique so that the number of samples obtained was 29 samples. The instrument used was a test of procedure text writing for 90 minutes, with topics determined by the students. The students’ writings were analyzed using procedural text writing rubric related to the generic structure and language feature of the text. Based on this research, students' ability in writing procedure texts was in category 3 (good). Although the ability of students to write procedure texts was in category 3 (good) by looking to the generic structure and language feature of the text, there are several parts of the text that students have not understood how to write them. Students were expected to understand how to write a good procedure text by paying attention to the generic structure and language feature of the text.